KOMITMEN ORGANISASI MEMODERASI PENGARUH KOMPLEKSITAS TUGAS PADA AUDIT JUDGMENT - Lusi Setyandarini Surya, Luh Putu; Dwirandra, A.A. N.B; Suputra, I.D.G Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.05.TAHUN 2017, 2017)
Auditor’s perspective in response of information is directly correspond to the responsibility and audit risk that auditor face in relation to their judgment. One factor that affects the auditor perception in evaluating information is the task complexity. Previous research suggests that task complexity is not consistently affecting audit judgment. The aim of t this research is to t gather empirical t evidence t of t the effect of t task complexity t on t audit judgment with organizational commitment as moderating variables. The sample for this research is taken with census sampling method. The data were collected by using questionnaire, given to 62 auditors who work at Public accountant firm all over the Province of Bali. The data were analyzed t using t Simple t Linear Regression t and Moderated Regression Analysis (MRA). The result showed that task complexity is negatively affecting audit judgment however, the organizational commitment is not u able u to u moderate the i effect of task complexity i on i auditi judgment.
Keywords: audit judgment, task complexity, organizational commitment